LEADERSHIP ROLE AND MOTIVATION TOWARDS THE PERFORMANCE OF EMPLOYEES OF THE NUTRITION INSTALLATION OF FATMAWATI CENTRAL GENERAL HOSPITAL WITH WORK ENVIRONMENT AS INTERVENING VARIABLE - Martinus Bangapadang, Adrial; Ahmad Badawi Saluy; Abdul Bari; Novawiguna Kemalasari (Dinasti International Journal of Digital Business Management, 2022)
Nowadays, for an organization or company at this time, it can be said that human resources have an important role or function. Fatmawati Central General Hospital (RSUP) is a government-owned hospital located in South Jakarta. The purpose of this study was to analyze the effect of leadership and motivation on employee performance at the Nutrition Installation of RSUP Fatmawati with the work environment as an intervening variable. This research is quantitative. The population in this study were employees of the Nutrition Installation of RSUP Fatmawati. The number of respondents in this take a look at amounted to seventy-seven respondents. In this study, the method for analyzing data was using the Structural Equation Model-SEM with SmartPLS-Partial Least Square. In this research, the method for analyzing data uses Structural Equation Model-SEM with SmartPLS-Partial Least Square. Based on the research test, it shows that there is a positive and significant influence on each hypothesis, namely leadership on the work environment, motivation on the work environment, leadership on performance, motivation on performance. The workplace is able to mediate the influence of leadership and motivation on employee performance at the Nutrition Installation of RSUP Fatmawati.